2020
DOI: 10.1111/cea.13568
|View full text |Cite
|
Sign up to set email alerts
|

A thymic stromal lymphopoietin polymorphism may provide protection from asthma by altering gene expression

Abstract: Background Genome‐wide association studies have identified associations of the single nucleotide polymorphism rs1837253 in the thymic stromal lymphopoietin (TSLP) gene with asthma, allergic disease and eosinophilia. The TSLP gene encodes two isoforms, long and short, and previous studies have indicated functional differences between these two isoforms. Objective We investigated the expression of these TSLP isoforms in response to a pro‐inflammatory signal, and the role of the rs1837253 genotype in gene isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…The role of TSLP in asthma is underscored by genome-wide association studies that have identified associations between asthma risk and single-nucleotide polymorphisms (SNPs) in the TSLP gene [38][39][40]. These include rs1837253 [41,42], which has been shown to regulate TSLP production in nasal epithelial cells [43] and influence asthma manifestation [44]. TSLP has also been implicated in aspirin-exacerbated respiratory disease (AERD), which is characterized by asthma, chronic rhinosinusitis with nasal polyps, and intolerance of cyclooxygenase-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The role of TSLP in asthma is underscored by genome-wide association studies that have identified associations between asthma risk and single-nucleotide polymorphisms (SNPs) in the TSLP gene [38][39][40]. These include rs1837253 [41,42], which has been shown to regulate TSLP production in nasal epithelial cells [43] and influence asthma manifestation [44]. TSLP has also been implicated in aspirin-exacerbated respiratory disease (AERD), which is characterized by asthma, chronic rhinosinusitis with nasal polyps, and intolerance of cyclooxygenase-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between IL-4 and IL-13 have been reported on the mouse macrophages responsiveness to TSLP [98]. Whatever the interpretation of these results, given the relevance of TSLP [99][100][101][102][103][104] and T H 2 cytokines in the pathogenesis of asthma [105,106], it is likely that these observations have translational relevance contributing to clinical manifestations of chronic inflammatory lung disorders.…”
Section: Discussionmentioning
confidence: 86%
“…We have finally entered the much‐anticipated era of personalized medicine for asthma, and several articles evaluated biologics and the variation in individual response to these in people with asthma 25‐27 , 28‐36 , 37 , 38 Others evaluated more traditional treatments for asthma, such as corticosteroids or mechanisms that may underlie impaired airway function in asthma 39‐59 . New interventions studied in clinical trials included air cleaners, triple inhaler therapy, an oral prostaglandin D2 antagonist 60‐62 and other more preliminary data from various interventions, from cinnamon and bacterial peptides to allergen immunotherapy 63‐67 .…”
Section: Asthmamentioning
confidence: 99%